2021
DOI: 10.1177/14614448211012374
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone use and academic performance: First evidence from longitudinal data

Abstract: To study the causal impact of smartphone use on academic performance, we collected – for the first time worldwide – longitudinal data on students’ smartphone use and educational performance. For three consecutive years, we surveyed all students attending classes in 11 different study programmes at two Belgian universities on general smartphone use and other drivers of academic achievement. These survey data were merged with the exam scores of these students. We analysed the resulting data by means of panel dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…That is, time spent on smartphone applications might reasonably be considered time that is not invested in intended actions, such as studying. This interpretation matches the consensual definition of procrastination (i.e., an irrational, voluntary delay to starting or completing an intended course of action; Steel, 2007) and sits well with research showing that both procrastination (Steel & Klingsieck, 2016) and (passively logged) smartphone use (e.g., Amez et al, 2019) are associated with poorer study outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…That is, time spent on smartphone applications might reasonably be considered time that is not invested in intended actions, such as studying. This interpretation matches the consensual definition of procrastination (i.e., an irrational, voluntary delay to starting or completing an intended course of action; Steel, 2007) and sits well with research showing that both procrastination (Steel & Klingsieck, 2016) and (passively logged) smartphone use (e.g., Amez et al, 2019) are associated with poorer study outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…It enables a permanent access to information and social interaction and facilitates many tasks of everyday life. However, an excessive use of the many possibilities can negatively influence well-being, physical health, and different areas of a person's offline life (Amez et al, 2019;Elhai et al, 2019a;Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, smartphone use time and problematic use were negatively linked to academic performance in young students (Lepp et al, 2014(Lepp et al, , 2015; their association with academic procrastination was positive (Yang et al, 2019). In a longitudinal study, an increase of smartphone use time positively predicted a decrease in academic achievement of students over a 3-year period (Amez et al, 2019).…”
mentioning
confidence: 94%
“…Given the impact of COVID-19, students in China had to stay at home more and take online classes, which provided them more opportunities to use smartphones and, therefore, more chances to use them for non-class-related purposes, which is especially true for younger students who often lack self-control. As a result, students were under a more substantial tension in time trade-off between smartphone use and study activities [ 14 , 15 ]. Because overuse of smartphones for non-class-related activities (e.g., playing video games, watching online TV series) may hamper study-related activities (e.g., engaging in solving mathematics problems).…”
Section: Introductionmentioning
confidence: 99%
“…However, some negative behaviors (e.g., PSU) harm students’ mathematics learning [ 2 , 19 , 29 ]. Most existing studies have found a negative association between PSU and students’ general academic performance, with a dominant focus on undergraduates [ 5 , 8 , 11 , 14 , 38 ]. For example, Kates et al [ 11 ] conducted a meta-analysis on the relationship between PSU and academic performance over 10 years (2008–2017), and 80% of the reviewed articles used a sample of undergraduates.…”
Section: Introductionmentioning
confidence: 99%